Dampak Pengembangan Kemasan terhadap Minat Beli - Adrian N, Nikolaus Elvan; Agung, Angelia; Lison, Enrico; Lokita, Ivana; Prawira, Matthew Ethan; Luis, Richardo; Marsha, Qinthara; Chandra M., Nany (Journal Pemberdayaan Masyarakat Indonesia, 2022)
MSME or micro, small, medium enterprise is a type of business that plays a very important role for Indonesia’s economy. Due to its large number, making sure that those businesses have decent performances will be a huge priority for the country in order to make a stable and active economy for its people. However, compared to businesses who carry out activities in big cities, there are also SMEs in rural areas who do not have the convenience and opportunities of those entrepreneurs with supporting facilities and knowledge. Which is why the group/writer, who’s a participant of the community development program, aims to provide assistance to MSMEs in the Cageur Village region in Kuningan in order to identify problems or constraints and try to formulate solutions so that the business’ performance increases. The results of mentoring showed that it had affected the business positively in various aspects such as improvements in marketing, operation and finance. The group focused on the discussion of analyzing the impact of product packaging development using several methods and found a correlation between the group’s improvisation on the business’ packaging and the increased interest of consumers buying the products.